Evaluasi Kinerja Website Pemerintah Kabupaten Pekalongan: Studi Kasus pada Website OPD Pekalongan - Diajeng Larasati; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study evaluates the performance of Regional Apparatus Organization (OPD) websites of the Pekalongan Regency Government in supporting the dissemination of public information. The evaluation was conducted using spesific criteria, including speed, accessibility, best practices, and search engine optimization (SEO). The method used in this study is the evaluation method, which involves the systematic collection and analysis of processes based on the defined criteria. The data obtained are measured against established standards to produce recommendations aimed at improving the quality of the websites. The research results show that the OPD websites perform well in terms of speed and implementation of best practices. However, the aspects of SEO and accessibility still require action to ensure that information can be easily accessed by the public, thereby supporting transparency and accountability in delivering public services.